Pre-FFT and post-FFT adaptive antenna array for OFDM transmission over cognitive radio network - Wan Mohd Zuferi , Wan Nadzlia Shazwanie; Ramli , Nordin; Mohamad, Hafizal; Abdullah, Khaizuran (2012)
This paper presents the joint interference cancellation and equalization for space-time block coded (STBC) orthogonal frequency division multiplexing (STBC-OFDM) transmission over underlay cognitive radio network. In this work, pre- and post-FFT adaptive antenna array is employed at secondary user receiver to find optimum antenna weights that place nulls at the primary transmitters. The paper discusses the performance of using both systems in STBC-OFDM receiver and presents the optimum weight determination for beamformers based on the minimum mean square error (MMSE) criteria. Simulation results demonstrate that post-FFT is optimum in terms of maximizing signal-to-noise-and-interference power ratio (SINR) and provides a lower bit error rate (BER) under existence of several primary users.